Modulation of cosmic rays at different cutoff rigidity - Agarwal,Rekha; Mishra,Rajesh K. (Sociedade Brasileira de Física, 2008)
The present work deals with the study of first three harmonics of cosmic ray intensity on geo-magnetically quiet days over the period 1981-1993 for Deep River and Inuvik neutron monitoring stations having mid and low cutoff rigidity. The amplitude of first harmonic remains high for Deep River having mid cutoff rigidity as compared to Inuvik neutron monitor having low cutoff rigidity on quiet days. The diurnal amplitude significantly decreases and phase shifts towards an earlier time during solar activity minimum years at both Deep River and Inuvik. The amplitude of second harmonic significantly enhanced during solar activity minimum as well as maximum at Deep River and remains low during solar activity maximum at Inuvik, whereas the phase shifts towards an earlier time during solar maximum for both the stations. The amplitude of the third harmonic significantly enhanced during solar activity minimum at Deep River and on solar activity minimum at Inuvik, whereas the phase does not show any significant characteristics and fluctuates quite frequently. The amplitude of semi/tri-diurnal anisotropy has a good positive correlation, while the others (i.e. amplitude and phase) have very weak correlation with solar wind velocity on quiet days at Deep River station during 1981-1993. The solar wind velocity significantly remains in the range 350 to 425 km/s i.e. being nearly average on quiet days. The amplitude and direction of the anisotropy on quiet days are weakly dependent on high-speed solar wind streams for two neutron monitoring station of mid and low cutoff rigidity threshold. The amplitude as well as direction of second harmonic has a good anti-correlation with IMF Bz and the product V x Bz on quiet days at Deep River station. However, the direction of second and third harmonic has a good anti-correlation with IMF Bz and the product V x Bz on quiet days at Inuvik station.